Wal-Mart and Carrefour's Retail Internationalisation Failure in South Korea: Application of Institutional Theory - Kim, Joon Hwan (2008)
This research argues that although the importance of the host country environments of a foreign country on retail internationalisation failure is acknowledged, there is scant understanding of the subject. Therefore, developing from previous studies, this study formulates an institutional framework to assist a systematic explanation of the subject. The framework will be developed by adopting Scott (2001)'s Neo Institutional Theory, thus categorising the host country environments under the dimensions of regulative,normative and cognitive pressures. The framework is then applied to examine the cases of Wal-Mart and Carrefour's retail internationalisation failure in South Korea.This will not only examine the applicability of the framework but will also add our overall understanding of South Korean discount store market. In result, the case study finds that the institutional framework developed in this research proved to be a useful guidance, and that all three dimensions of Korean retail environment found to have caused Wal-Mart and Carrefour's failure to gain retail legitimacy, and ultimately, a retail internationalisation failure. This explorative categorisation method is expected to allow future researchers from embarking a systematic analysis of the effect of the host country environments on international retailers. The study finishes by offering recommendations on how future researches must develop from here.